ADMINISTRATION OF TICAGRELOR IN THE CATH LAB OR IN THE AMBULANCE FOR NEW ST ELEVATION MYOCARDIAL INFARCTION TO OPEN THE CORONARY ARTERY (Неотложная медицинская помощь)
Montalescot G., van ‘t Hof A.W., Lapostolle F., et al. Prehospital ticagrelor in ST-segment elevation myocardial infarction // N. Engl. J. Med. – 2014. – Vol. 371. – P. 1016–1027.